STRATEGI PENERJEMAHAN VERBA AKTIF: ANALISIS TERHADAP TEKS MUTHALA’AH KITAB AL-QIRAAH AL RASYIDAH KARYA ABDUL FATTAH SHOBRI DAN ALI UMAR - Hifni, Ahmad; Zahira, Ghefira; Wulandari, Tiyassifa Putri (Kementerian Sekretariat Negara Republik Indonesia, 2024)
This research aims to explain the translation strategy of active verbs (fi'il mabni ma'lūm) from Arabic texts to Indonesian texts as well as to present variations in the structure and writing patterns of active verbs in Arabic. The method used is qualitative method based on library research. The data source used is the Arabic text taken from the book Al-Qirā'ah Al-Rashidah by Abdul Fattah Shobri and Ali Umar. The researcher uses Arabic as the source language (BSu) and Indonesian as the target language (BSa) in this translation process. From the discussion described, some equivalents or translations of active verbs into passive verbs were found. It is seen in thirteen data of fi'il mabni ma'lūm contained in the text of Al-Qirā'ah Al-Rashidah. This study concludes that fi'il mabni ma'lūm in Arabic does not always translate into active sentences in Indonesian. Although the form in the Arabic text is an active verb, but sometimes, it is more appropriate to be translated in the form of passive sentences, following the structure and grammar of Indonesian which is more flexible and acceptable.